2017
DOI: 10.1002/fut.21866
|View full text |Cite
|
Sign up to set email alerts
|

Economic significance of commodity return forecasts from the fractionally cointegrated VAR model

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 45 publications
0
39
0
2
Order By: Relevance
“…Pandey and Vipul (2017) established long-run relationship between underlying and the futures prices of eight commodities and concluded that price efficiency originates from futures price, while information content in each commodity is different. Dolatabadi et al (2018) examine the long-run relationship between 17 commodities for the period from 1983 to 2012. The study establishes a long-run relationship among the commodities but do not examine the existence of structural break within the period of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey and Vipul (2017) established long-run relationship between underlying and the futures prices of eight commodities and concluded that price efficiency originates from futures price, while information content in each commodity is different. Dolatabadi et al (2018) examine the long-run relationship between 17 commodities for the period from 1983 to 2012. The study establishes a long-run relationship among the commodities but do not examine the existence of structural break within the period of the study.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we employ the permanent‐transitory (PT) decomposition of Gonzalo and Granger (1995) to identify the common permanent component of each pair of variances. To facilitate the PT decomposition, we follow Dolatabadi, Narayan, Nielsen, and Xu (2018) by constructing a fully specified framework which accommodates long‐run and short‐run effects in a system containing fractionally cointegrated variables. Such a framework is afforded by the fractionally cointegrated vector autoregressive (FCVAR) model of Johansen (2008) and Johansen and Nielsen (2012) as follows Δd(Xtμ)=αβΔdbLb(Xtμ)+falsefalsec=1kΓcΔdLbc(Xtμ)+εt where Xt denotes the pair of variances under analysis, Δd and Lb, respectively represent the fractional difference operator and the fractional lag operator.…”
Section: Resultsmentioning
confidence: 99%
“…For its part, Eduardo Rossi and Santucci de Magistris (2013) applied this methodology to study the relationship between spot and futures markets, and Maggie E. C. Jones, Morten Ørregaard Nielsen, and Michał Ksawery Popiel (2014) checked the fractional long-run relationship between Canadian political support and macrovariables. Additionally, Sepideh Dolatabadi, Nielsen, and Ke Xu (2016) and Dolatabadi et al (2018) applied the FCVAR model for the analysis of price discovery in commodity markets, and more recently, Leandro Maciel (Forthcoming) modelled and forecasted daily high and low asset prices. Few studies in the literature have addressed the application of this methodology in the interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%